In vitro antiviral potential of Ocimum basilicum and Olea europaea leaves extract against Newcastle Disease Virus of poultry: Sarah A. H. Al-Amri1@, Shony M. Odisho1 and Orooba M.S. Ibrahem2 - Al-Amri1, Sarah A. H. (The Iraqi Journal of Veterinary Medicine, 2015)
This study was carried out to investigate the effect of using alcoholic Ocimum basilicum and Olea europaea leaves extract, to study the antiviral activity against the Newcastle disease virus of poultry chicken embryo fibroblast monolayer culture. The extract was also decided for the chicken fibroblast culture and the concentrations (500, 250, 125, 100 and 50 µg /ml) of an alcoholic extract of Ocimum basilicum and Olea europaea leaves in maintenance media appeared to be nontoxic. Where the cytopathic effects of the Newcastle disease virus on chicken embryo fibroblast monolayer culture are well established so these concentrations were used to detect the antiviral activity of Ocimum basilicum and Olea europaea in addition to in vitro, pre and post -inoculative treatment of fibroblast cells with plant extracts to get an idea of viral reduction titer in cell tissue culture. Absence of cytopathic effects in monolayer cell culture and virus titer reduction were used as an indicative of antiviral activity of extract of Ocimum basilicum and Olea europaea leaves. In vitro, pre and post -inoculative treatment of fibroblast cells with plant extracts showed that leaves of Ocimum basilicum, and Olea europaea had antiviral activities of Newcastle disease virus at 500 and 250 µg/ml. In conclusion the viral reduction titer was found range between 10-6 to 10-1 with 500 µg /ml of Olea europaea and Ocimum basilicum extract as compared to 10-7 with virus control.